The Effect of Testing Chamber on the Response Patterns of an array of Gas Sensor in Sensing Robusta Coffee Aroma from Bangsalsari and Sidomulyo, Jember - Asnawati, Asnawati; Siswoyo, Siswoyo; Ningsih, Febiola Silvia; Ainiyah, Qurotul; Zulfikar, Zulfikar; Mulyono, Tri; Muflihah, Yeni Maulidah (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
The gas sensor performance can be improved by optimizing the testing chamber design, including volume, shape, gas inlet/outlet positions, and sensor array. We studied the effect of chamber design on the gas sensor's response patterns characteristics in differentiating Robusta coffee aroma from Sidomulyo, and Bangsalsari, Jember. Hemisphere and cylindrical chambers, with three variations for each model, and a ring chamber, were used as model chambers. Eight types of gas sensors (MQ-135, MQ-136, MQ-2, MQ-3, MQ-6, MQ-7, MQ-8, and MQ-9) were used in the sensor array system to examine the gas sensor instrument performance. The resulting responses were analyzed using the reproducibility, response time, and principal component analysis (PCA) test. The result shows that the reproducibility value for all hemisphere chamber models, cylindrical chamber model-1, and ring chamber indicated an excellent sensor performance (%RSD<20%). Meanwhile, the cylindrical chambers model-2 and 3 resulted in %RSD>20%, indicating the low performance of the gas sensor. Among all variations, hemisphere chamber model-1, a hemisphere chamber with the inlet position lower than the outlet gas position, has the best performance due to the shortest response time, high-intensity signal, and performing ability to distinguish the response patterns characteristics of Robusta coffee aroma from Sidomulyo and Bangsalsari, Jember, Indonesia. In this study, we found that changing the testing chamber design, volume, and inlet/outlet position resulting different gas sensor responses to the coffee aroma. The proposed instrument can distinguish the coffee aroma from a different origin.